Experimental study of airless spray jet breakup at elevated temperature and pressure - Naz, M.Y. (2013)
The presented research work was focused onto the understanding of the jet behavior of the sprays of heated water during the low pressure atomization process. This task was accomplished using an in-house built intermittently forced liquid spraying system capable of lowering the liquid viscosity and surface tension to a desired value and then atomizing it into a full cone spray patterns in the ambient air surrounding. Using a high speed camera, the jet breakup dynamics were visualized as a function of system input parameters. The analysis of the grabbed images confirmed the strong influence of these processing parameters on full cone spray characteristics. It was also predicted that heated liquids generate a dispersed spray pattern by utilizing the partial evaporation of the spraying medium that is the induction of thermal energy enhances the jet disintegration ability. The spray cone width and angle did not vary significantly whereas the Weber and Reynolds numbers along with other nozzle flow parameters showed an appreciable response to the load pressure and temperature at early stages of water injection. The ultimate objective of the work was to understand and control the airless spray jet breakup mechanism under reduced load pressure and high water temperature. Â© (2013) Trans Tech Publications, Switzerland.